IMPLEMENTASI KURIKULUM MERDEKA PADA SEKOLAH PENGGERAK DI SEKOLAH DASAR - Siti Mutia Rusmana; Yantoro; Isaura Sherly Pamela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the steps, planning, implementation and evaluation in the implementation of the Independent Curriculum at State Elementary School 64/IV Jambi City which was implemented in the odd semester of 2024/2025. This research was conducted at SDN 64/IV Jambi City for more than months. Data collection was carried out by means of observation, interviews, and documentation studies. After the data was collected, the data was analyzed using a phenomenological approach and type. The results of the study indicate that the implementation of the Independent Curriculum has brought significant changes in learning methods, which are more flexible and student-centered. Teachers feel challenges in adaptation, especially related to resource readiness, understanding of curriculum concepts, and technical support. However, various strategies are applied, such as collaboration between educators, independent training, and the use of technology to support learning. Overall, the Independent Curriculum has a positive impact on students' creativity and independence, although it still requires more optimal policy support. This study provides insight for policy makers, educators, and schools in increasing the effectiveness of the implementation of the Independent Curriculum.